Development of SERASI media to represent the philosophical values of Kretek Dance and its impact on elementary students’ learning outcomes - Tasya Wafiq Azizah; Deasylina da Ary (Research and Development in Education (RaDEn), 2025)
The limited availability of effective interactive media in dance education hinders practical learning implementation, necessitating the development of tailored instructional media to enhance learning effectiveness, efficiency, and relevance. This research aims to produce products resulting from technological developments, namely SERASI media in cultural arts subjects in the material of getting to know the environment with dance in class IV elementary school. This type of research is Research and Development with the ADDIE model. The results of SERASI media research obtained very good qualifications declared valid and effective as dance learning media in elementary schools with a percentage of teacher and student responses of (90.9%) and (96.88%), as well as (93.18%) from material experts and (88%) from media experts. It was stated in the T-test < 0, 05 with an n-gain of 0, 7087 so that SERASI media was declared effective and feasible to support dance learning to improve student learning outcomes in class IV SD 3 Tenggeles.